A full heat exchange membrane doped with functionalized ZIF-7 nanoparticles and preparation method thereof
By mixing the functionalized ZIF-7 nanoparticles in the full thermal exchange membrane, using the interface aggregation method to build a selective "micro channel", solving the "trade-OFF" problem between existing membranes between humidity and gas blockage , Realize the performance of efficient wetness, gas resistance and thermal recovery.
Patent Information
- Application Number
- CN202210741057.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-06-27
AI Technical Summary
The existing full heat exchange membrane has a "trade-off" between improving moisture permeability and gas barrier properties, and the agglomeration of nanoparticles leads to interfacial voids and gas leakage, reducing gas barrier properties.
The functional ZIF-7 nanoparticle is used. The interface aggregation method is mixed with nanoparticles in the polyamine separation layer to regulate the interactive force of the interface interface to avoid the interface gap, and build a rapid transmission selective "micro channel".
A full thermal exchange membrane with high dampness, high resistance and high fever recovery efficiency, enhance the mechanical performance and flame retardant performance of the membrane, reduce the transmission rate of the CO2 gas, while maintaining the efficiency of high -pyreces exchange.
Smart Images

Figure CN115282782B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of moisture permeability, gas barrier and heat recovery, and specifically relates to a full heat exchange membrane doped with functionalized ZIF-7 nanoparticles and a preparation method thereof. Background Art
[0002] Nearly one-third of my country's electricity consumption is used in residential buildings and shopping malls, and nearly half of the electricity is used for air conditioning. In addition, people spend more than 80% of their time indoors, so ventilation is extremely important during the frequent use of air conditioning. From the perspective of saving energy, protecting the environment and physical health, ventilation systems using the principle of total heat exchange energy saving play an important role in maintaining human health and energy saving. While using outdoor fresh air to exchange indoor polluted air (such as carbon dioxide, formaldehyde and other harmful gases) to improve indoor air quality, in order to reduce the energy required to adjust the temperature of fresh air, scientists have designed a total heat exchanger as the core equipment of the energy-saving fresh air system to recover energy between outdoor fresh air and indoor polluted air. With the rapid development of membrane technology, the total heat exchanger with membrane as the heat recovery medium can achieve good energy recovery and gas (such as CO2) barrier effect under the premise of ensuring ventilation effect under the modification of ZIF nanoparticles.
[0003] The total heat exchanger uses the total heat exchange membrane as a medium to achieve high-efficiency recovery through sensible heat exchange and latent heat exchange. There is no mass transfer process in sensible heat exchange, and only the fresh air and exhaust air are transferred through energy, resulting in temperature changes; while latent heat exchange is the exchange of water vapor mass between the fresh air and the exhaust air, thereby adjusting the water vapor concentration in the air, causing an increase or decrease in the latent heat of water vapor, and achieving the purpose of energy saving. Since the latent heat of vaporization of water vapor in the air is very high, the energy proportion in humid air is relatively large. Therefore, the latent heat contribution rate of the total heat exchange of indoor and outdoor air is much greater than the sensible heat contribution rate. Therefore, in order to improve the energy recovery rate of the total heat exchanger and ensure fresh air in the enclosed space, it is an important research direction to improve the moisture permeability and gas barrier properties of the total heat exchange membrane.
[0004] At present, the core component of the full heat exchange equipment, the full heat exchange membrane, is mostly made of commercial paper membrane, which has the following disadvantages: 1. The paper membrane is a fully permeable membrane that cannot effectively block CO2 gas and has poor mechanical properties; 2. The paper membrane is not flame retardant and is prone to mold during use, causing secondary pollution to the air; 3. There is a "trade-off" between moisture permeability and gas barrier properties. The composite polyamide full heat exchange membrane constructed by interfacial polymerization has boundary defects and different degrees of gas leakage. Previous attempts have been made to add nanoparticles such as montmorillonite, silica, and ZIF-7 to the membrane, hoping to improve the moisture permeability of the membrane by increasing the hydrophilicity of the membrane or constructing selective "micro channels" in the membrane. However, due to the agglomeration of nanoparticles, the membrane will have interfacial gaps and gas leakage, resulting in reduced gas barrier properties of the membrane. In order to obtain a full heat exchange membrane with ultra-high gas barrier, it is necessary to find a reasonable treatment method on the basis of ensuring heat exchange efficiency. Summary of the invention
[0005] In order to overcome the shortcomings of the existing full heat exchange membrane, the present invention provides a full heat exchange membrane doped with functional ZIF-7 nanoparticles and a preparation method thereof. The full heat exchange membrane of the present invention is composed of an ultrafiltration membrane support layer, a polyamide separation layer and functionalized ZIF-7 nanoparticles distributed in the polyamide layer. The preparation process is: adding functionalized ZIF-7 nanoparticles to the oil phase, and forming a polyamide ultra-thin separation layer to which functionalized ZIF-7 nanoparticles are added by an interfacial polymerization method. Functionalized ZIF-7 nanoparticles can effectively regulate the phase interface interaction force, avoid interfacial voids, increase the density of the membrane, accurately construct a fast transmission selective "microscopic channel", and at the same time increase the mechanical properties and flame retardant properties of the membrane, increase the surface roughness of the membrane, and increase the surface area of the separation layer, thereby improving moisture permeability, gas barrier and heat recovery efficiency. The full heat exchange membrane prepared by the present invention has the characteristics of high moisture permeability, high gas barrier and high heat recovery efficiency, and the preparation method is simple and feasible, easy to operate, and can be applied to air energy recovery, indoor air purification, fresh air system and chemical environmental protection fields, and has good industrial application prospects.
[0006] The technical solution of the present invention is as follows:
[0007] A total heat exchange membrane doped with functional ZIF-7 nanoparticles, comprising: an ultrafiltration membrane support layer, a polyamide separation layer, and functionalized ZIF-7 nanoparticles distributed in the polyamide layer;
[0008] The ultrafiltration membrane support layer can be prepared from one or more of polysulfone, polyethersulfone, polyetherketone, polyarylsulfone, polyacrylonitrile, and polyvinylidene fluoride;
[0009] The ultrafiltration membrane contains holes with a diameter of 1nm to 0.2μm, a small part of the polyamide is located in the holes of the ultrafiltration membrane, and most of the polyamide is located on one side surface of the ultrafiltration membrane.
[0010] The polyamide separation layer is prepared by interfacial polymerization of aqueous phase amine monomers and oil phase acyl chloride monomers;
[0011] The functionalized ZIF-7 nanoparticles include but are not limited to one or more combinations of functionalized ZIF-7 nanoparticles such as ZIF-7-NH2, ZIF-7-OH, ZIF-7-CH3, ZIF-7-CH2OH, ZIF-7-C2H5, and ZIF-7-C3H7; the particle size of the functionalized ZIF-7 nanoparticles is between 20 and 500 nm.
[0012] A method for preparing a total heat exchange membrane doped with functional ZIF-7 nanoparticles, the preparation method comprising:
[0013] (1) Synthesis of functionalized ZIF-7 nanoparticles
[0014] The metal precursor solution and the ligand solution are mixed, stirred and reacted at room temperature (20-30°C) for 0.5-12h, and then the nano-scale solid particles are collected by centrifugation, washed (with methanol), and vacuum dried (50-120°C, 6-12h) to obtain functionalized ZIF-7 nanoparticles;
[0015] The concentration of the metal precursor solution is 0.01-1 mol / L, the solvent is DMF (N,N-2 methylformamide), and the metal precursor is selected from one or more of zinc oxide, zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, etc.;
[0016] The concentration of the ligand solution is 0.01-1 mol / L, the solvent is methanol, and the ligand is a mixture of benzimidazole and benzimidazole containing a functional group; the benzimidazole containing a functional group is selected from one or more of 2-aminobenzimidazole, 2-hydroxybenzimidazole, 2-methylbenzimidazole, 2-hydroxymethylbenzimidazole, 2-ethylbenzimidazole, 2-propylbenzimidazole and the like;
[0017] The volume ratio of the metal precursor solution to the ligand solution is 1:1;
[0018] (2) Preparation of membrane solution
[0019] At room temperature, dissolving the amine monomer in deionized water to prepare an aqueous phase solution, dissolving the acyl chloride monomer in an organic solvent and adding the functionalized ZIF-7 nanoparticles obtained in step (1), and uniformly dispersing by ultrasonication to obtain an oil phase solution for later use;
[0020] In the aqueous phase solution, the mass fraction of the amine monomer is 0.01-5% (preferably 1-3%), and the amine monomer includes but is not limited to one or more of piperazine, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, ethylenediamine, hexamethylenediamine, 1,4-butylenediamine, 4,4-diaminodiphenyl ether, 4,4-diaminodiphenylmethane, o-benzylamine, 1,2-propylenediamine, 1,3-propylenediamine, 2,4-diaminotoluene, 1,2-cyclohexanediamine, 4,5-dichloro-o-phenylenediamine, diethylenetriamine, mesitylenetriamine and their derivatives;
[0021] In the oil phase solution, the mass fraction of the acyl chloride monomer is 0.01-5% (preferably 0.1-0.5%), the mass fraction of the functionalized ZIF-7 nanoparticles is 0.001-5% (preferably 0.03-1%), the organic solvent is selected from one or more alkanes such as n-hexane, n-heptane, n-octane, n-dodecane, isododecane, isohexadecane, etc., and the acyl chloride monomer includes but is not limited to one or more of isophthaloyl chloride, terephthaloyl chloride, phthaloyl chloride, trimesoyl chloride, polyaromatic sulfonyl chloride and derivatives thereof;
[0022] (3) Preparation of polyamide layer by interfacial polymerization
[0023] At room temperature, the ultrafiltration membrane support layer is first immersed in an aqueous solution for 1 to 10 minutes (preferably 2 to 5 minutes), then the excess aqueous solution on the membrane surface is removed, and then the ultrafiltration membrane support layer is immersed in an oil phase solution for 20 seconds to 10 minutes (preferably 30 seconds to 2 minutes) to cause an interfacial polymerization reaction, and then the ultrafiltration membrane support layer is taken out and dried in the air to form a polyamide layer with functionalized ZIF-7 nanoparticles added on the surface of the ultrafiltration membrane support layer;
[0024] (4) Post-processing
[0025] The membrane is heat-treated at 50-90° C. (preferably 60-80° C.) for 5-30 min (preferably 8-20 min) to obtain a total heat exchange membrane doped with functional ZIF-7 nanoparticles.
[0026] The types of the total heat exchange membrane doped with functional ZIF-7 nanoparticles prepared by the invention include flat membrane, hollow fiber homogeneous membrane or hollow composite membrane and tubular membrane.
[0027] The beneficial effects of the present invention are:
[0028] By regulating the ligand structure of ZIF-7 nanoparticles, the functionalization of ZIF-7 nanoparticles was achieved, and functionalized ZIF-7 particles were successfully added during the interfacial polymerization process. The functionalized ZIFs nanoparticles were doped in the polyamide separation layer, which can effectively regulate the phase interface interaction force, avoid interfacial voids, accurately construct fast transmission selective "microscopic channels", and at the same time increase the mechanical properties of the membrane, increase the surface roughness of the membrane, and increase the surface area of the separation layer, thereby improving the moisture permeability, gas barrier and heat recovery efficiency.
[0029] Functionalized ZIF-7 nanoparticles interact with polyamide (PA) membranes by forming hydrogen bonds or coordination bonds, thereby increasing binding affinity without introducing serious defects. Therefore, ZIFs nanoparticles can be fixed in and on the surface of the polyamide layer to accurately construct fast transmission selective "micro channels"; at the same time, the nanoparticles can be fine-tuned by surface functionalization and controlling crystal size and morphology to achieve high moisture permeability and high gas barrier properties.
[0030] The total heat exchange membrane doped with functional ZIF-7 nanoparticles of the present invention has higher moisture permeability, gas barrier and heat recovery performance than the total heat exchange membrane prepared by adding unfunctionalized ZIFs nanoparticles, and the preparation method is simple and feasible, easy to operate, and is suitable for air total heat recovery, air conditioning and heating energy recovery, indoor air purification, air dehumidification and heat and moisture recovery, and chemical environmental protection fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a process flow chart for preparing the total heat exchange membrane doped with functionalized ZIF-7 nanoparticles.
[0032] Figure 2 are electron microscope images of the polyamide separation layers prepared in (a) Comparative Example 1, (b) Example 3, (c) Example 5, and (d) Example 6;
[0033] Figure 3 It is the infrared image of ZIF-7 nanoparticles and functionalized ZIF-7 nanoparticles.
[0034] Figure 4 These are performance test graphs of the blank total heat exchange membrane of Example 1, the total heat exchange membrane doped with unfunctionalized ZIF-7 nanoparticles of Example 2, and the total heat exchange membranes prepared in Examples 1-6, wherein (a) is a graph of water vapor and CO2 permeability, and (b) is a graph of total heat exchange efficiency data. DETAILED DESCRIPTION
[0035] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.
[0036] The indoor environment for preparing all the full heat exchange membranes in the examples is: temperature 25° C., humidity 45%, and normal pressure.
[0037] The polysulfone ultrafiltration membrane support layer used in the examples was purchased from Hangzhou Water Treatment Center.
[0038] Embodiment 1:
[0039] A total heat exchange membrane doped with functional ZIF-7 nanoparticles is prepared. The specific steps of the preparation method are as follows:
[0040] (1) Dissolve 5 mmol Zn(NO3)2·6H2O in 50 ml DMF to prepare Zn 2+ Solution; dissolve 5mmol benzimidazole and 5mmol 2-aminobenzimidazole in 50ml methanol to prepare imidazole solution; pour the imidazole solution into Zn 2+ The solution was stirred for 6 hours to obtain a milky white ZIF-7-NH2 dispersion. The obtained nano-sized ZIF-7-NH2 particles were collected by high-speed centrifugation, washed with methanol to obtain pure ZIF-7-NH2, and vacuum dried at 120°C for 12 hours to obtain solid powdered ZIF-7-NH2;
[0041] (2) First, the ultrafiltration membrane support layer is immersed in a 2wt% MPD (meta-phenylenediamine) solution for 3 minutes to form an aqueous liquid layer on its surface. After being taken out, the excess aqueous solution on the membrane surface is dried. Then, the ultrafiltration membrane support layer is immersed in a 0.1wt% TMC (trimethylenediamine) and 0.05wt% ZIF-7-NH2 n-hexane solution for 1 minute to allow interfacial polymerization reaction to occur. The ultrafiltration membrane support layer is taken out and dried in the air. Then, it is heat treated at 70°C for 15 minutes and dried to obtain a full heat exchange membrane doped with amino-functionalized ZIF-7 nanomaterials.
[0042] The water vapor permeability, CO2 permeability and enthalpy exchange efficiency of the total heat exchange membrane doped with amino-functionalized ZIF-7 nanoparticles prepared in Example 1 are shown in Figure 4 , water vapor permeability is 571.71GPU, CO2 permeability is 16.72GPU, wet exchange is 43.76%, enthalpy exchange efficiency is 62.73%, and heat exchange is 96.08%.
[0043] Embodiment 2:
[0044] The rest of Example 2 is the same as that of Example 1, except that 5 mmol of 2-aminobenzimidazole in step (1) of Example 1 is replaced by 5 mmol of 2-hydroxybenzimidazole;
[0045] The water vapor permeability, CO2 permeability and enthalpy exchange efficiency of the functionalized ZIF-7 nanomaterial modified full heat exchange membrane prepared in Example 2 are shown in Figure 4, water vapor permeability is 580.24GPU, CO2 permeability is 27.93GPU, wet exchange is 44.83%, enthalpy exchange efficiency is 63.51%, and heat exchange is 96.91%.
[0046] Embodiment 3:
[0047] The rest of Example 3 is the same as that of Example 1, except that 5 mmol of benzimidazole in step (1) of Example 1 is replaced by 5 mmol of 2-methylbenzimidazole;
[0048] The water vapor permeability, CO2 permeability and enthalpy exchange efficiency of the functionalized ZIF-7 nanomaterial modified full heat exchange membrane prepared in Example 3 are shown in Figure 4 , water vapor permeability is 614.61GPU, CO2 permeability is 34.09GPU, wet exchange is 45.59%, enthalpy exchange efficiency is 63.03%, and heat exchange is 96.88%.
[0049] Embodiment 4:
[0050] The rest of Example 4 is the same as that of Example 1, except that 5 mmol of benzimidazole in step (1) of Example 1 is replaced by 5 mmol of 2-hydroxymethylbenzimidazole;
[0051] The water vapor permeability, CO2 permeability and enthalpy exchange efficiency of the functionalized ZIF-7 nanomaterial modified full heat exchange membrane prepared in Example 4 are shown in Figure 4 , water vapor permeability is 587.63GPU, CO2 permeability is 21.46GPU, wet exchange is 43.64%, enthalpy exchange efficiency is 61.97%, and heat exchange is 96.08%.
[0052] Embodiment 5:
[0053] The rest of Example 5 is the same as that of Example 1, except that 5 mmol of benzimidazole in step (1) of Example 1 is replaced by 5 mmol of 2-ethylbenzimidazole;
[0054] The water vapor permeability, CO2 permeability and enthalpy exchange efficiency of the functionalized ZIF-7 nanomaterial modified full heat exchange membrane prepared in Example 5 are shown in Figure 4 , water vapor permeability is 623.06GPU, CO2 permeability is 27.86GPU, wet exchange is 46.19%, enthalpy exchange efficiency is 63.73%, and heat exchange is 96.77%.
[0055] Embodiment 6:
[0056] The rest of Example 6 is the same as that of Example 1, except that 5 mmol of benzimidazole in step (1) of Example 1 is replaced by 5 mmol of 2-propylbenzimidazole;
[0057] The water vapor permeability, CO2 permeability and enthalpy exchange efficiency of the functionalized ZIF-7 nanomaterial modified full heat exchange membrane prepared in Example 6 are shown in Figure 4 , water vapor permeability is 624.65GPU, CO2 permeability is 20.42GPU, wet exchange is 45.88%, enthalpy exchange efficiency is 62.42%, and heat exchange is 96.75%.
[0058] The polyamide separation layers prepared in Examples 3, 5 and 6 are as follows: Figure 2 As shown in (b), (c), and (d), obvious functionalized ZIFs nanoparticles can be seen on the polyamide layer, and the particle size is between 30 and 200 nm.
[0059] Comparative Example 1:
[0060] Step (1): first immerse the ultrafiltration membrane support layer in a 2 wt % MPD solution for 3 min to form an aqueous phase layer on its surface, and then remove the excess aqueous phase solution on the membrane surface;
[0061] Step (2): The ultrafiltration membrane support layer was immersed in a 0.1 wt% TMC n-hexane solution for 1 min to cause an interfacial polymerization reaction, and then taken out and air-dried, and then heat-treated at 70° C. for 10 min and dried to obtain a blank full heat exchange membrane.
[0062] Figure 2 (a) is an electron microscope image of the polyamide separation layer prepared in Comparative Example 1. Only the polyamide layer without nanoparticles can be seen in the electron microscope image.
[0063] The water vapor permeability, CO2 permeability and enthalpy exchange efficiency of the full heat exchange membrane prepared in Comparative Example 1 without adding ZIFs nanoparticles are shown in Figure 4 , water vapor permeability is 586.07GPU, CO2 permeability is 152.59GPU, wet exchange is 40.35%, enthalpy exchange efficiency is 60.83%, and heat exchange is 95.15%.
[0064] Comparative Example 2:
[0065] Comparative Example 2 is the same as Example 1, except that 5 mmol of benzimidazole and 5 mmol of 2-aminobenzimidazole in step (1) of Example 1 are replaced with 10 mmol of benzimidazole;
[0066] The water vapor permeability, CO2 permeability and enthalpy exchange efficiency of the full heat exchange membrane doped with unfunctionalized ZIF-7 nanoparticles prepared in Comparative Example 2 are shown in Figure 4 , water vapor permeability is 589.05GPU, CO2 permeability is 77.49GPU, wet exchange is 42.76%, enthalpy exchange efficiency is 61.91%, and heat exchange is 95.99%.
[0067] The CO2 permeability test conditions of all embodiments and comparative examples are: temperature 25°C, tested by pressure difference method; enthalpy exchange efficiency test conditions: fresh air temperature 35°C, RH40%; exhaust air temperature 25°C, RH25%.
[0068] The total heat exchange membrane doped with functionalized ZIF-7 nanoparticles of the present invention is characterized by adding functionalized ZIF-7 nanoparticles into an oil phase, and using an interfacial polymerization method to form an ultra-thin cortex of polyamide doped with functionalized ZIF-7 nanoparticles, thereby ensuring high moisture permeability, high gas barrier and high heat recovery efficiency. Compared with the comparative example, it not only has an extremely low CO2 gas permeability (10-40GPU), but also maintains the same enthalpy exchange efficiency (60-65%). At the same time, the preparation method is simple, feasible, easy to operate, and low in cost, and can be applied to air energy recovery, gas separation, indoor fresh air system and chemical environmental protection fields.
[0069] The present invention is not limited to the above embodiments. As long as the requirements of the present invention are met, they belong to the protection scope of the present invention.
Claims
1. A method for preparing a total heat exchange membrane doped with functionalized ZIF-7 nanoparticles, characterized in that: A total heat exchange membrane doped with functionalized ZIF-7 nanoparticles is prepared as follows, comprising an ultrafiltration membrane support layer, a polyamide separation layer and functionalized ZIF-7 nanoparticles; The polyamide separation layer is distributed on the surface and inside the pores of the ultrafiltration membrane support layer; The functionalized ZIF-7 nanoparticles are distributed in the polyamide separation layer; The material of the ultrafiltration membrane support layer is one or more of polysulfone, polyethersulfone, polyetherketone, polyarylsulfone, polyacrylonitrile and polyvinylidene fluoride; The functionalized ZIF-7 nanoparticles include one or more of ZIF-7-NH2, ZIF-7-OH, ZIF-7-CH3, ZIF-7-CH2OH, ZIF-7-C2H5, and ZIF-7-C3H7, and the particle size thereof is 20 to 500 nm; The type of the total heat exchange membrane is a flat membrane, a hollow fiber homogeneous membrane or a hollow composite membrane and a tubular membrane; The preparation method of the above-mentioned full heat exchange membrane doped with functional ZIF-7 nanoparticles is as follows: (1) Synthesis of functionalized ZIF-7 nanoparticles The metal precursor solution and the ligand solution are mixed and reacted at room temperature by stirring, and then the nano-scale solid particles are collected by centrifugation, washed with methanol, and vacuum dried to obtain functionalized ZIF-7 nanoparticles; (2) Preparation of membrane solution At room temperature, dissolving the amine monomer in deionized water to prepare an aqueous phase solution, dissolving the acyl chloride monomer in an organic solvent and adding the functionalized ZIF-7 nanoparticles obtained in step (1), and uniformly dispersing by ultrasonication to obtain an oil phase solution for later use; (3) Preparation of polyamide layer by interfacial polymerization At room temperature, the ultrafiltration membrane support layer is first immersed in an aqueous solution for 1 to 10 minutes, then taken out to remove excess aqueous solution on the membrane surface, and then immersed in an oil solution for 20 seconds to 10 minutes to cause an interfacial polymerization reaction, and then taken out to dry in the air to form a polyamide layer containing functionalized ZIF-7 nanoparticles on the surface of the ultrafiltration membrane support layer to obtain a composite membrane; (4) Post-processing Heat treating the composite membrane obtained in step (3) at 50-90° C. for 5-30 min to obtain a full heat exchange membrane doped with functional ZIF-7 nanoparticles; The concentration of the ligand solution is 0.01-1 mol / L, the solvent is methanol, and the ligand is one of a mixture of benzimidazole and 2-aminobenzimidazole, a mixture of benzimidazole and 2-hydroxybenzimidazole, a mixture of 2-methylbenzimidazole and 2-aminobenzimidazole, a mixture of 2-hydroxymethylbenzimidazole and 2-aminobenzimidazole, a mixture of 2-ethylbenzimidazole and 2-aminobenzimidazole, and a mixture of 2-propylbenzimidazole and 2-aminobenzimidazole.
2. The method for preparing a total heat exchange membrane doped with functionalized ZIF-7 nanoparticles according to claim 1, characterized in that: In step (1), the volume ratio of the metal precursor solution to the ligand solution is 1:1, and the stirring reaction conditions are: stirring at 20-30°C for 0.5-12h; and the vacuum drying conditions are: drying at 50-120°C for 6-12h.
3. The method for preparing a total heat exchange membrane doped with functionalized ZIF-7 nanoparticles according to claim 1, characterized in that: In step (1): The concentration of the metal precursor solution is 0.01-1 mol / L, the solvent is N,N-2-methylformamide DMF, and the metal precursor is selected from one or more of zinc oxide, zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate.
4. The method for preparing a total heat exchange membrane doped with functionalized ZIF-7 nanoparticles according to claim 1, characterized in that: In step (2): In the aqueous phase solution, the mass fraction of the amine monomer is 0.01-5%, and the amine monomer includes but is not limited to one or more of piperazine, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, ethylenediamine, hexamethylenediamine, 1,4-butylenediamine, 4,4-diaminodiphenyl ether, 4,4-diaminodiphenylmethane, o-benzylamine, 1,2-propylenediamine, 1,3-propylenediamine, 2,4-diaminotoluene, 1,2-cyclohexanediamine, 4,5-dichloro-o-phenylenediamine, diethylenetriamine, and mesitylenetriamine; In the oil phase solution, the mass fraction of the acyl chloride monomer is 0.01-5%, the mass fraction of the functionalized ZIF-7 nanoparticles is 0.001-5%, the organic solvent is selected from one or more of n-hexane, n-heptane, n-octane, n-dodecane, isododecane, and isohexadecane, and the acyl chloride monomer includes one or more of isophthaloyl chloride, terephthaloyl chloride, phthaloyl chloride, trimesoyl chloride, and polyaromatic sulfonyl chloride.
5. The method for preparing a total heat exchange membrane doped with functionalized ZIF-7 nanoparticles according to claim 1, characterized in that: In step (3), the ultrafiltration membrane support layer is immersed in the aqueous solution for 2 to 5 minutes, and immersed in the oil solution for 30 seconds to 2 minutes.
6. The method for preparing a total heat exchange membrane doped with functionalized ZIF-7 nanoparticles according to claim 1, characterized in that: In step (4), the post-treatment temperature is 60-80°C and the time is 8-20 min.
Citation Information
Patent Citations
Preparation method of aromatic polyamide film modified by ZIF-8 type metal-organic framework material
CN104209021A
Preparation method of total heat exchange membrane based on interface polymerization anti-diffusion growth ZIF
CN113694741A